Applied studies of some Southern African blowflies (Diptera: Calliphoridae) of forensic importance - Lunt, Nicola (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2003)
Three major aspects of blowfly (Diptera: Calliphoridae) research were the focus of this study. Firstly, the phylogenetic relationships of 40 oestroid species from a variety of geographical localities were investigated using Cytochrome Oxidase b subunit I (COl) gene sequences. Maximum parsimony (MP) and Jukes-Cantor neighbor-joining (NJ) analyses both extracted a paraphyletic Calliphoridae, with the Calliphorinae-Luciliinae clade being sister to the Sarcophagidae. Short branch lengths within Chrysomya indicate a recent rapid radiation of this genus. Phormia and Protophormia either formed a sister clade to Chrysomya, or were embedded in this genus. Tree topologies were comparable between MP and NJ trees, but the positions of some genera were ambiguous. Secondly, developmental parameters and behaviour were investigated for four southern African species of forensically important blowflies viz. Chrysomya chloropyga, C. putoria, C. megacephala and Lucilia sericata, and ad hoc observations were made for Calliphora croceipalpis, Chrysomya marginalis and the predatory C. albiceps. Choice of oviposition substrate differed between species, mirroring substrate preferences in the field. Sexual dimorphism and dwarfism within a cohort complicated ageing maggots using size, but the use of developmental events (e.g. ecdysis) allowed ages to be determined unambiguously. Separate species status was supported for the previously synonymised C. chloropyga and C. putoria, by differences in maggot behaviour, larval growth rates and temperature optima. The proportion of total development time assigned to each larval instar and pupariation was variable among temperatures, but similar between congeneric species. Thirdly, since a negative linear relationship was found to occur between the developmental constant (K) and developmental zero (D₀) for both Calliphoridae and Sarcophagidae, the potential for predicting physiological parameters of unstudied taxa was investigated. Species and genera of Palaearctic origin generally had high K's and low D₀'s, and the reverse was true for the tropical taxa. It was found that both K and D₀ can be estimated for "unknown" taxa using the Felsenstein's Independent Contrasts (FIC) method of PDTree (Garland et al. 200 I), provided that branch lengths are relatively short and the phylogenetic position of the estimated taxon is unambiguous.
Keywords: Diptera -- South Africa; Blowflies -- South Africa; Forensic entomology